Coach Competence in Coaching Implementation in SMDP Training Pusdiklat PT. KAI - Mellyawati, Elly; Sudiapermana, Elih; Sardin, Sardin (Indonesian Journal of Adult and Community Education, 2024)
The addition of a coaching program is seen to have a better effect on employees because it prioritizes two-way communication and explores solutions from employees themselves for every problem that arises so that it is considered more effective. This study aims to analyze the relationship between coach competencies seen from the dimensions of active listening, creating awareness, direct communication and coachee learning motivation through a coaching process to achieve a coaching effectiveness. This is in line with the theory that says coaching can be very effective in helping individuals reach their true potential. Descriptive quantitative approach is the method used in this study. Data was collected using questionnaires from 90 respondents taken using a simple random sampling approach. The results showed that the direct communication dimension was the strongest dimension of coach competence, while the motivation to learn in the coachee showed diversity.